Vielfalt und Chancengerechtigkeit an Hochschulen : Wie gelingt ein wirksames Diversity Management? - Kastell, Kirstin (Universität Rostock, 2017)
Institutions of higher education need to fulfil the legal mandate to provide equal opportunities and equity: The diversity of their students and employees should be considered, all university members should have equal access to full participation in research and teaching, and existing disadvantages are to be eliminated through Diversity Management. However, discrepancy prevails between these requirements and the universities’ efforts on the one hand and perpetuated structural inequalities on the other. The paper examines the diversity-relevant paragraphs of two recently amended university laws (North Rhine-Westphalia and Schleswig-Holstein) as well as the argumentative resistance generated against the introduction of diversity commissioners. On the premise that institutions of higher education are structured by power formations, three approaches of effective Diversity Management are presented with particular regard to their being capable of altering anchored power relations. In a last step, the paper elaborates a participation-oriented Diversity Management.
Keywords: Antidiskriminierung; Chancengleichheit; Diversität; Diversity Management; Partizipation; 378 Hochschulbildung; Antidiscrimation; Equity; Equal Opportunities; Diversity; Mainstreaming; Participation